Africans Need not Miss Out on the Benefits of Globalisation - Bonaglia, Federico (OECD Publishing, 2007)
Strong commodity prices are driving Africa's growth, which should be about 6 % in 2007 and 2008. External vulnerability is a function of its limited integration into international trade and investment flows. Africa should mobilise external sources more strategically. In this respect, aid for trade can be import. * This Policy Insights introduces the African Economic Outlook 2007
Keywords: Development